Genetic Aspects of Congenital and Idiopathic Scoliosis - Giampietro, Philip F. (Hindawi Publishing Corporation, 2012)
Congenital and idiopathic scoliosis represent disabling conditions of the spine. While congenital scoliosis (CS) is caused by morphogenic abnormalities in vertebral development, the cause(s) for idiopathic scoliosis is (are) likely to be varied, representing alterations in skeletal growth, neuromuscular imbalances, disturbances involving communication between the brain and spine, and others. Both conditions are characterized by phenotypic and genetic heterogeneities, which contribute to the difficulties in understanding their genetic basis that investigators face. Despite the differences between these two conditions there is observational and experimental evidence supporting common genetic mechanisms. This paper focuses on the clinical features of both CS and IS and highlights genetic and environmental factors which contribute to their occurrence. It is anticipated that emerging genetic technologies and improvements in phenotypic stratification of both conditions will facilitate improved understanding of the genetic basis for these conditions and enable targeted prevention and treatment strategies.